2021
DOI: 10.11591/ijece.v11i3.pp2477-2489
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid load balance based on genetic algorithm in cloud environment

Abstract: Load balancing is an efficient mechanism to distribute loads over cloud resources in a way that maximizes resource utilization and minimizes response time. Metaheuristic techniques are powerful techniques for solving the load balancing problems. However, these techniques suffer from efficiency degradation in large scale problems. This paper proposes three main contributions to solve this load balancing problem. First, it proposes a heterogeneous initialized load balancing (HILB) algorithm to perform a good tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…The proposed method achieves good performance by assigning optimal tasks to virtual machines suitable for different scenarios (as shown in Figure 12). Figure 15 shows a comparison of the performance of the proposed method with previous methods [14,32,46]. As shown in Figure 15, the performance of the proposed method is better than other existing methods.…”
Section: Comparison Of the Proposed Methods With Previousmentioning
confidence: 93%
“…The proposed method achieves good performance by assigning optimal tasks to virtual machines suitable for different scenarios (as shown in Figure 12). Figure 15 shows a comparison of the performance of the proposed method with previous methods [14,32,46]. As shown in Figure 15, the performance of the proposed method is better than other existing methods.…”
Section: Comparison Of the Proposed Methods With Previousmentioning
confidence: 93%
“…It is also observed that the total cost can be reduced through an energy consumption model that is composed of the processor's execution and transmission cost [7]. Furthermore, the improvement of the load deviation, the resource utilisation (RU) and the makespan can be achieved through the proposed algorithm in the paper [8] denoted hybrid load balance based on genetic algorithm (HLBGA). Similarly, resource utilisation, load balancing, and excellent performance can also be achieved by implementing a novel architecture that is based on the particle swarm optimisation (PSO) and the dynamic dispatch queues algorithms [2].…”
Section: Int J Elec and Comp Eng Issn: 2088-8708mentioning
confidence: 99%
“…However, this approach lacks the issue of overloading the virtual machine. Recent work in a similar direction by [22] presented heterogeneous initialized workload balancing for task scheduling.…”
Section: Introductionmentioning
confidence: 99%